Combination Therapy of 5-Fluorouracil and Triamcinolone Acetonide with Compression Therapy after Surgical Excision in the Management of Keloids in Ears - Randeep Singh Lamba; Pinki Pargal; Anurag Salwan; Junaise P.M; Pallavi Nigam; Noopur Bansal (Indian Journal of Plastic Surgery)
Background Any deviation from the normal process of wound healing leads to excessive scar formation in the form of keloid or hypertrophic scar.